Normative Theory and Descriptive Psychology in Understanding Causal Reasoning: The Role of Interventions and Invariance - James F. WOODWARD (Artefactos, 2020)
This paper explores some relationships between, on the one hand, normative philosophical theories of causation and causal reasoning and, on the other hand, descriptive theories of causal cognition of the sort produced in psychology. These issues are discussed from the perspective of an interventionist account of causation. The focus is on what I call distinctions among causal relationships in terms of such features as invariance, specificity and proportionality and the psychological significance of these. It is argued that normative and descriptive theorizing about causation have a great deal to learn from each other.